Improving Teaching and Learning in Technical Teacher and Instructor Training Institutions in Uganda: Implication of Learning Theories - Ddungu-Kafuluma , Mukasa John (African Journal of Education,Science and Technology (AJEST), 2018)
The paper explores the extent to which learning theories are applied in the training of technical teachers and instructors in Uganda, ascertains those theories that are relevant. Data was collected from 238 respondents, including 145 students, 81 instructors and 12 principles and Ministry of Education and Sports (MOES) officials. Respondents were selected using purposive and convenience sampling. Structured questionnaires, interview guides and an observation schedule were used. Findings show that learning theories are not infused into the training of technical teachers and instructors. Learning theories were perceived by trainers as pure theory that had little application to technical teacher education. Respondents agreed that learning theories enable teachers to acquire professional skills and that they promote hands-on training. Respondents further agreed that constructivism, cognivitism and behaviorism can ensure high quality and effective teaching and learning in technical teacher education. The paper advocates for, a complete re-thinking of the design and implementation of Technical and Vocational Education (TVE) teacher training in Uganda to infuse in the three learning theories. Technical and Vocational Education and Training (TVET) teacher training in Uganda should open up to new and effective teaching and learning approaches that are based on the principles of learning theories. This will subsequently improve the quality of TVE teachers and instructors in Uganda.